2023
DOI: 10.3892/etm.2023.11886
|View full text |Cite
|
Sign up to set email alerts
|

Propofol reduces lipopolysaccharide‑induced cardiomyocyte injury in sepsis by activating SIRT1‑mediated autophagy

Abstract: Myocardial injury is an indicator of poor prognosis in sepsis, whereas propofol has been reported to protect the myocardium. Therefore, the present study investigated the effect of propofol on myocardial injury in sepsis and its mechanism. An in vitro model of myocardial cell injury was established in myocardial H9C2 cells using lipopolysaccharide (LPS). The Cell Counting Kit 8 (CCK8) assay was used to investigate the effect of propofol pretreatment on the viability of normal and LPS-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In this study, SIRT1 was found to be a downstream target of propofol by TargetNet prediction, and the study confirmed that propofol can act on SIRT1 [20]. Therefore, this paper investigated whether propofol improves POCD by acting on SIRT1 and its downstream signaling.…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…In this study, SIRT1 was found to be a downstream target of propofol by TargetNet prediction, and the study confirmed that propofol can act on SIRT1 [20]. Therefore, this paper investigated whether propofol improves POCD by acting on SIRT1 and its downstream signaling.…”
Section: Introductionmentioning
confidence: 51%
“…This suggests that propofol may promote SITR1 expression by binding to SIRT1. Moreover, although most current studies have reported the ability of propofol to activate SIRT1, the site at which propofol binds and activates SIRT1 has not been reported [20,38,39]. Crystal structures of several sirtuin inhibitor complexes reveal that EX527 occupies the nicotinamide site and a neighboring pocket, making contact with the ribose of NAD(+) or the coproduct 2'-O-acetyl-ADP ribose [40].…”
Section: Discussionmentioning
confidence: 96%